The experiences of mothers whose children take Ritalin for the treatment of ADHD (Attention Deficit Hyperactivity Disorder) - Jacobs, L.J. (University of Pretoria, 2013)
Dissertation (MA (Counselling Psychology))--University of Pretoria, 2006.